The Processing of Household Waste by Residents of Griya Serpong Housing Complex, Serpong Sub-District, South Tangerang, Indonesia, in Compliance With Law Number 18 of 2008 and Law Number 32 of 2018 - Suryani, Reni; Sa’adah, Nur; Lubis, Ilhamsyah (Sinergi International Journal of Law, 2023)
The Waste Management Law Number 18 of 2008 mandates waste management at various levels, including producers, communities, industrial areas, traditional markets, and malls. Local government administrations in regencies and cities need to create or revise regional regulations (Perda) and design a communal-based waste management masterplan. Until now, waste management has largely been centralized, with an open dumping system at the final disposal site, which ended in 2013. There are three forms of urban waste management: centralization, decentralization, and centralization-decentralization. An ideal waste management pattern is neither purely centralized nor decentralized, but rather a combination of both. Organic Waste Management Facilities (OWMF) are established at the source of dominant waste generation (initial stage), with a recycling system similar to City Waste Management Facilities (CWMF) to support and assist in marketing the products of the OWMF established by Joint Business Groups (KUB) formed by the community, known as the "self-sustaining concept." Addressing the waste problem requires an examination of the current waste management practices to identify areas where improvements and enhancements can be made, so that only waste that truly cannot be recycled ends up in the final disposal site, such as hazardous waste (B3) that is incinerated directly. This research aims to provide a solution to the waste disposal issue, which is largely centralized in Indonesia.